Pollinia as "pseudopalpi" on Archisepsis in Costa Rica: accidental or opportunistic? - Marshall, Stephen A. (2022)
Male sepsids carrying pollinia as pseudopalpi were observed at three separate bait stations (small dung baits set out to attract other flies) about 500m apart along a side trail in the Peninsula Sector of Parque Nacional Volcan Arenal. Several pollinia-laden males were seen engaged in agonistic interactions and some pollinia-bearing males were seen alone; one individual was seen bubbling (egesting a bubble of fluid) with the paired pollinia flanking the bubble. No flies were seen with pollinia adhering to any structure other than the mouthparts and the bubbling individual was the only apparent female observed with pollinial "pseudopalpi".